KARAKTERISTIK BREM BALI YANG DIBUAT DENGAN MENSUBSTITUSI BERAS KETAN PUTIH DENGAN UMBI UBI JALAR MERAH - Wisaniyasa, Ni Wayan (Agrotekno, 2007)
The purpose of this research to determine the characteristic of brem Bali made with various level of red sweet potato substitution. This experiment used Completely Randomized Design with three replications with a total of 15 experiment units. The treatments were : 1. 100% red sweet potato without glutinous rice. 2. 75% red sweet potato and 25% glutinous rice. 3. 50% red sweet potato and 50% glutinous rice. 4. 25% red sweet potato and 75% glutinous rice. 5. Without red sweet potato and 100% glutinous rice. Results showed that ethanol, methanol, acetic acid, ash, Ca and Zn content were significantly different. Brem Bali produced by 100% red sweet potato contained ethanol, acetic acid, ash, Ca and Zn 4,18% v/v, 5,48% w/v, 0,66% w/w, 0,070 ppm, and 0,788 ppm respectively. In the other hand, Brem Bali produced by 100% glutinous rice contained ethanol, acetic acid, ash, Ca, and Zn are 11,38 % v/v, 1,52% w/v, 0,23% w/w, 0,007 ppm and 0,015 ppm respectively. The heavy metals content of brem Bali were low and not harmful. In this experiment methanol, Pb and As were not found. Sweet potato cannot substitute glutinous rice for “Brem Bali’ materials.